Moskaus (in)existente Mittelschicht Eine Ethnographie - Braun, Bernhard (2022)
The Russian ,middle class' has been heavily researched since the end of the Soviet Union, which is mainly rooted in its attributed socio-political functions as a catalyst of democratic and market-economic transformations in post-socialist Russia. This book abandons these transitological, sometimes one-dimensional, one-size-fits-all approaches by not reifying a priori defined categories but rather approaching it by long-term ethnographic fieldwork and thus the book takes a look behind the façade of a much-cited concept and allows for a deeper understanding of Russian society.